2020
DOI: 10.1080/2574254x.2020.1752596
|View full text |Cite
|
Sign up to set email alerts
|

Family-based prevention of overweight and obesity in children aged 2–6 years: a systematic review and narrative analysis of randomized controlled trials

Abstract: Overweight and obesity in childhood are highly preventable and parents are key role models in the establishment of healthy behaviours. The aim of this study was to assess the effectiveness of family-based interventions for prevention of overweight and obesity in children aged 2-6 years. A systematic literature search was performed in the databases such as Medline, PsycInfo, Family Study Abstracts, Embase, and CINAHL, published between 2010 and May 2019. The eligible studies were preventive randomised controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…A recent systematic review of 39 randomized controlled trials (RCTs) for preventing obesity, mostly delivered in high‐income countries and at preschools, found that there is moderate evidence that multicomponent trials in children aged from 0 to 5 years reduce zBMI 4 . There are, however, few family‐based interventions involving both caregivers and children in the primary care setting for children aged 2–6 years that show an effect in reducing BMI and report on cost‐effectiveness 4,10 . Economic evaluations with a societal perspective, examining both direct costs, such as healthcare costs, and indirect costs, such as caregivers' time costs and productivity losses, are important for decision makers to be able to prioritize among increasingly limited public resources, even when the effect size of an intervention does not reach statistical significance 5,11,12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of 39 randomized controlled trials (RCTs) for preventing obesity, mostly delivered in high‐income countries and at preschools, found that there is moderate evidence that multicomponent trials in children aged from 0 to 5 years reduce zBMI 4 . There are, however, few family‐based interventions involving both caregivers and children in the primary care setting for children aged 2–6 years that show an effect in reducing BMI and report on cost‐effectiveness 4,10 . Economic evaluations with a societal perspective, examining both direct costs, such as healthcare costs, and indirect costs, such as caregivers' time costs and productivity losses, are important for decision makers to be able to prioritize among increasingly limited public resources, even when the effect size of an intervention does not reach statistical significance 5,11,12 …”
Section: Introductionmentioning
confidence: 99%
“…4 There are, however, few family-based interventions involving both caregivers and children in the primary care setting for children aged 2-6 years that show an effect in reducing BMI and report on cost-effectiveness. 4,10 Economic evaluations with a societal perspective, examining both direct costs, such as healthcare costs, and indirect costs, such as caregivers' time costs and productivity losses, are important for decision makers to be able to prioritize among increasingly limited public resources, even when the effect size of an intervention does not reach statistical significance. 5,11,12 From the family perspective studies show that caregivers want an early and structured response from health professionals when their child is identified with overweight, and they ask for easily understood information based on the needs and literacy level of the family.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for overweight in early childhood are multifactorial (Al Yazeedi & Berry, 2019; Larque et al, 2019), and interventions to prevent overweight in a child from developing into obesity need to embrace this complexity (McAdams, 2010). Several reviews have shown effectivity in various interventions for preventing obesity in overweight children, although not all interventions were proven effective and several studies have a high risk of bias (Colquitt et al, 2016; Landgren et al, 2020; Narzisi & Simons, 2020; Peirson et al, 2015; Waters et al, 2011). Furthermore, for an intervention to be implemented in everyday clinical practice, it needs to be feasible from the perspective of healthcare services and healthcare professionals (Eno Persson et al, 2018; Waters et al, 2011) and solid evidence is important for interventions implemented into child health services (CHS).…”
Section: Introductionmentioning
confidence: 99%
“…Grandparent involvement in child obesity prevention and treatment interventions has been sparsely mentioned in the literature. Several systematic reviews (Ash et al, 2017; Landgren et al, 2020; Wang et al, 2015) have been conducted to summarize the characteristics and success of child obesity interventions. These researchers agree that school-based interventions, involving parents and delivering, at minimum, nutrition and physical activity components have been most successful.…”
Section: Discussionmentioning
confidence: 99%